SISTEM INFORMASI CINDERAMATA IMPLEMENTASI E-COMMERCE UNTUK PENGEMBANGAN DESA WISATA SENDANGASRI KABUPATEN REMBANG - Muhammad Tahwin; Dian Ayu Liana Dewi; Fajar Sodiq (Buletin Abdi Masyarakat, 2024)
Sendangasri Village is one of the tourist villages in Rembang Regency, Central Java. As a tourism village, Sendangasri Village has a variety of handicraft and culinary products that can be developed to support the development of a tourism village. The results of observations made by the Service Team found the fact that the marketing of these handicraft and culinary products was manual, that is, the public or tourists had to come directly to Sendangasri Village. Based on the analysis conducted by the Service Team, it can be seen that the problems faced by the Sendangasri Tourism Village are: (1) The lack of knowledge of the tourism village manager about e-commerce, (2) Human resources who lack skills in managing information systems as a Products marketing media on Sendangasri Tourism Village, (3) There is no information system that serves the public or potential tourists to shop online. The solution offered is the implementation of e-commerce in the form of a Souvenir Information System and training that can improve the skills of tourism village managers in serving online transactions. The result of community service in the Sendangasri Tourism Village is that the tourism village manager has been able to use the Souvenir Information System to support the development of the Sendangasri Tourism Village.Key word : Ecommerce, Souvenir Information System,Development